PELAKSANAAN MEDIASI DALAM PENYELESAIAN PERSELISIHAN PEMUTUSAN HUBUNGAN KERJA DI DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI ROKAN HULU - Aidil Rahmat Fauzan; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The process of resolving disputes through mediation is emphasized in the deliberations oragreements of the parties, so that there is no element of coercion between the parties and mediators, theparties request voluntarily to the mediator to help resolve the conflict. Therefore, a mediator domiciledhelps the parties to reach an agreement that can only be decided by the parties to the dispute. The mediatoris an employee of a government agency responsible for the field of labor who fulfills the requirements as amediator determined by the Minister to carry out mediation and has the obligation to provide written adviceto the disputing parties to resolve rights disputes, interest disputes, termination of disputes, and disputesbetween trade unions / labor unions in only one company.From the results of the research that the authors did, it can be concluded that the stages ofmediation at the Office of Social Services, Manpower and Transmigration in Rokan Hulu Regency were inthe stage of recording disputes, determining mediators to handle cases and research case files inaccordance with procedures stipulated by Law Number 2 of 2004 regarding Industrial Relations Disputes,but in the next stage, the calling of the parties is not in accordance with the provisions of the Law, namelymediators calling parties only through telephone calls which should be regulated by the parties sent aninvitation letter to attend the mediation session. Second, efforts that can be made to resolve industrialrelations disputes in the Social Service, Manpower and Transmigration Office of Rokan Hulu Regency canbe efficient and effective by increasing the trust of the parties to the mediator, increasing the number ofmediators and increasing the mediator's abilities and expertise, and making space a special session formediation that is clean and adequate.Keywords: Mediation - Disputes - Termination of Employment.